ПРОБЛЕМА НЕУСПІШНОСТІ МОЛОДШИХШКОЛЯРІВ У СУЧАСНИХ ПСИХОЛОГО-ПЕДАГОГІЧНИХ ДОСЛІДЖЕННЯХ - Долженко, Світлана (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті проаналізовано праці сучасних психологів та педагогів з проблеми неуспішності молодших школярів. Розглянуті психологічні, психофізіологічні, психолого-педагогічні фактори шкільної неуспішності дітей молодшого шкільного віку, описані особливості розвитку пізнавальної, мотиваційної, емоційної, довільно-регуляторної сфери учнів, які мають когнітивні труднощі у навчанні, та, як наслідок, неуспішність. Висвітлено методи та шляхи попередження шкільної неуспішності молодших школярів у сучасних психолого-педагогічних дослідженнях. В статье проанализированы труды современных психологов и педагогов по проблеме неуспеваемости младших школьников. Рассмотрены психологические, психофизиологические, психолого-педагогические факторы школьной неуспеваемости детей младшего школьного возраста, описаны особенности развития познавательной, мотивационной, эмоциональной, произвольно-регуляторной сферы учащихся, имеющих когнитивные трудности в обучении, и, как следствие, неуспеваемость. Освещены методы и пути предупреждения школьной неуспеваемости младших школьников в современных психолого-педагогических исследованиях. In the article labours of modern psychologists and teachers are analysed on issue of unprogress of junior schoolchilgren. The psychological, psychological, psychophsicological-pedagogical factors of school failure of children of midchildhood are considered, and describe particulary the development of cognitive, motivational, emotional, arbitrarily regulatory scope of students, who have cognitive learning difficulties as a consequence of the lack of success.The methods and ways to prevent school failure of junior schoolchildren are reflected in modern psychological and psychologopedagogical research. Thus, in connection with reformation of the modern system of education there is a task before society to changethe focus of pedagogical science appeared with the appeal of greater attention on personality development of students, on their individuality. It follows to spare the special attention methods, facilities, educational programs which are directed on opening of possibilities of every child, help them to be well argued fell a seeker and open new knowledges. In the evaluation of knowledge we should not forget the psychological characteristics of the child. An estimation for a child must be a long-awaited stimulus, but not punishment. An important role in studies is allotted parents, which largely, carry responsibility for the work-load of child optional employments, for attitude of child studies, personal interest by a process, for a desire to execute home tasks and go to school. If we considering all aspects of education and studies modern school can go to a new high-quality level. School failure is easily to prevent, than correct and remove.